2020
DOI: 10.1177/0255761420932689
|View full text |Cite
|
Sign up to set email alerts
|

Children’s verbal explanations of their visual representation of the music

Abstract: Recent findings in music research are increasingly confirming the embodied nature of music cognition. Assuming that a bodily engagement with music may affect the children’s musical meaning formation, we investigated how young children’s interaction with music, based on verbal description after listening versus body movement description while listening, may be reflected in the verbal explanation of their own visual representations of the music they listened to. In this study, 47 children (aged 9–10) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…The use of visual media in the classroom is nothing new. For decades, educators have recognized the benefits of visual materials to motivate students, increase their participation, and improve their learning (Fortuna & Nijs, 2020). As researchers investigate the exploitation of visual media and the efficacy of instructional pedagogies used by teachers, video recording is expected to be a useful tool.…”
Section: Visualization Strategy In Music Lesson Through Blended Learningmentioning
confidence: 99%
“…The use of visual media in the classroom is nothing new. For decades, educators have recognized the benefits of visual materials to motivate students, increase their participation, and improve their learning (Fortuna & Nijs, 2020). As researchers investigate the exploitation of visual media and the efficacy of instructional pedagogies used by teachers, video recording is expected to be a useful tool.…”
Section: Visualization Strategy In Music Lesson Through Blended Learningmentioning
confidence: 99%
“…Furthermore, the analysis indicated that children involved in listening combined with verbal-based activities used more varied elements in their post-test global drawings, such as symbols, shapes, and figurative images (e.g., castles and wolves), than at the start of the intervention. These findings suggest that learning activities based on different modalities of interaction affect the development of musical meaning making in different ways ( Fortuna and Nijs, 2020a , b ). It is important to note that the verbal learning activities in this study were not dialogic teaching strategies.…”
Section: Introductionmentioning
confidence: 97%
“… Fortuna and Nijs (2020a , b) compared the effects of movement-based activities (“show the music in body movements”) with verbal-based activities (“describe the music verbally”) on children’s (aged 9–10) graphical depictions of a composition (“describe the music with pencils”). After listening to Kangaroos by Saint-Saëns and drawing a representation of the music, the children were asked to explain their drawings in words.…”
Section: Introductionmentioning
confidence: 99%
“…Music listeners' personal meaning and their a wide range of emotions evoked through their interaction with music can be a pedagogical challenge for general music teachers. To scrutinize one's musical sense-making, extensive scholarly inquiry has underscored the importance of integrating drawing activities into part of music lesson plans (Carroll, 2018;Elkoshi, 2019;Fortuna & Nijs, 2020). Drawing can be an educational tool for capturing sounds and expressing students' varied learning experiences when listening to music (Reybrouck et al, 2009;Verschaffel et al, 2010).…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…From such perspective, the purpose of this action research study was to explore an integration of drawing activities into the Kodály instruction, built upon previous studies that have illuminated the transformative effect of drawing experiences on students' musical understanding (Carroll, 2018;Elkoshi, 2015Elkoshi, , 2019Fortuna & Nijs, 2020;Pitts, 2014). Prior studies have predominantly centered on student-invented drawings (e.g., Carroll, 2018;Elkoshi, 2015) or instrumental music contexts (e.g., Elkoshi, 2015).…”
Section: ⅰ Introductionmentioning
confidence: 99%